Flood Risk Assessment for Better City Resilience; Case of The Bab El Oued Agglomeration, Algiers (Algeria) - Taib, Lyes (Indonesian Journal of Social Science Research, 2024)
The concept of natural risk represents a challenge to the economic and social development of a given territory, which leads to the adoption of a rational and studied approach to addressing the critical situation imposed by risks. Flooding is one of the most dangerous phenomena, capable of causing enormous damage to life, the economy, and the environment. The locality of Bab el Oued experienced a painful episode in its history in terms of flood damage during the year 2001. The risk in this locality is classified as very high, which implies that it is necessary to continuously reassess preventive measures and disaster management strategies if flooding occurs. This should be based on both natural and human factors, making risk a devastating reality and a constraint on sustainable development. Through this article, attempts have been made to find intelligent solutions for flood disaster management in the highly threatened neighbourhood of Bab El Oued within the framework of current legislation and regulations, following a likely scenario.